SERVICES DIGITALIZATION PLAN IN LEGAL SERVICES COMPANIES (CASE STUDY VLADIMIR BASYAR FIRNANDA) - Andika Firnanda; Taufiq Amir (Sean Institute, 2023)
Nothing escapes or can escape the law, both in the public and private spheres, especially business activities by corporations, civil partnerships, as well as individuals. With all the problems that exist in society and along with the development of technology, it is a necessity that currently the legal services industry must be able to combine legal services with technology. This research outlines the digitalization plan for VBF Law Firm, which is to create a digital platform that enables customers to consult with legal experts through the firm's website. The objective of the digitalization plan is to improve customer experience and make legal services more accessible and convenient. The plan involves several key stages, including interviews with key persons, company assessment, marketing analysis, operational analysis, finance analysis and risk analysis. The idea is to create a user-friendly interface that enables customers to easily find information about legal services, access legal advice, and communicate with lawyers via chat, email, or video conferencing. In conclusion, the digitalization of VBF can provide a payback period of 9 months with a positive NPV and an IRR value of 200%, so it's worth investing in.